Automated Device for Uncapping Multiple-Size Bioanalytical Sample Tubes Designed to Reduce Technician Strain and Increase Productivity. (June 2021) - Jaeger, Jacob W.; Adkins, Scottland C.; Perez-Tamayo, Samuel C.; Werth, Katelyn E.; Hansen, Gregory; Nimunkar, Amit J.; Radwin, Robert G.
Technicians in a commercial laboratory manually uncap up to 700 sample tubes daily in preparation for bioanalytical testing. Manually twisting off sample tube caps not only is a time-consuming task, but also poses increased risk for muscle fatigue and repetitive-motion injuries. An automated device capable of uncapping sample tubes at a rate faster than the current workflow would be valuable for minimizing strain on technicians' hands and saving time. Although several commercial sample tube–uncapping products exist, they are not always usable for a workload that uses a mix of tube sizes and specific workflow. A functioning uncapping device was developed that can semi-automatically uncap sample tubes with three different heights and diameters and was compatible with the workflow in a commercial laboratory setting. Under limited testing, the average success rate with uncapping each of the three sample tube sizes or a mix of them was 90% or more, more than three times faster than manual uncapping, and met standard acceptance criteria using mass spectrometry. Our device with its current performance is still a prototype, requiring further development. It showed promise for ergonomic benefit to the laboratory technicians, however, reducing the necessity to manually unscrew caps.